Cytogenetic and epigenetic aberrations in peripheral lymphocytes of northwest Arkansas Marshallese. (3rd April 2023) - Ewing, Laura E.; Pathak, Rupak; Landes, Reid D.; Skinner, Charles M.; Binz, Regina; Young, Sean G.; Riklon, Sheldon; Stahr, Shelbie; Su, Joseph; Boerma, Marjan; McElfish, Pearl A.; Hauer-Jensen, Martin; et al.
Abstract: Purpose: Nuclear weapons testing in the northern Marshall Islands between 1946 and 1958 resulted in ionizing radiation (IR) exposure of the thousands of Marshallese. Furthermore, numerous islands were contaminated by radioactive fallout. Significant increases in cancer and metabolic syndrome incidences have been reported among Marshallese, and potential for further increases looms due to the latency of radiation-induced health effects. The purpose of this study was to investigate the genetic and epigenetic effects of exposure to IR that could be associated with radiation-induced disease among the Northwest Arkansas (NWA) Marshallese. Materials and Methods: We performed analysis of chromosomal aberrations and DNA methylation based on residential and exposure history of NWA Marshallese. Results: Analysis of chromosomal aberrations demonstrated higher incidence of genetic rearrangements in women with self-reported history of radiation exposure (95% CI: 0.10, 1.22; p =.022). Further clustering of study participants based on their residential history demonstrated that participants who spent substantial amounts of time (≥6 months) in the northern atolls (thus, in the proximity of nuclear tests) before 1980 had more chromosomal aberrations than their peers who lived only in the southern atolls (95% CI: 0.08, −0.95; p =.021), and that this difference was driven by women. A relationship between the time spent in the northern atolls and increase in chromosomal aberrations was observed: 0.31 increase in chromosomal aberrations for every 10 years spent at northern atolls (95% CI: 0.06, 0.57; p =.020). Finally, significant inverse correlations between the chromosomal aberrations and the extent of DNA methylation of four LINE-1 elements L1PA2, L1PA16, L1PREC1, and L1P4B were identified. Conclusions: The results of this study provide first evidence of the presence of stable genetic and epigenetic rearrangements in peripheral lymphocytes of NWA Marshallese and warrant further studies to analyze the role of radiation exposure in health disparities experienced by this Pacific Island nation.